Survival Rate and Associated Factors of Childhood Leukemia in Iran: A Systematic Review and Meta Analysis - Yousef Veisani; Ali Delpisheh (Mazandaran University of Medical Sciences, 2017)
Context Resent reviews have shown that about 18% of all child cancers are leukemia. Track of the survival rate can help researchers improve quality of life of patients through improving screening or discovery of better treatments. Objectives This review aimed at estimating the 5-year survival rates and associated factors of childhood leukemia in Iran. Data Sources We carried out a systematic review through search of relevant studies published in English (PubMed, Scopus, Google scholar, and ISI) and Persian databases (Magiran, Medlib, SID, and Iran Medex). Study Selection The study included all epidemiologic studies that estimated survival rate in children with leukemia in Iran during years 2002 to 2015, and a standardized manner was used for extraction of information. Data Extraction The entire text or summary of all searched articles was extracted and then, related articles were selected, and irrelevant ones were excluded. Fixed and random effects models were calculated by the STATA using standard meta-analysis methods. Heterogeneity was assessed by I² statistics. Results The overall 5-year survival rate in patients with childhood leukemia in Iran was 0.65 (95% CI, 0.62 to 0.67, 10 studies), in the acute lymphoblastic leukemia (ALL) subtype was 71.0% (95% CI: 68.0 to 74.0), and in the acute myeloid leukemia (AML) subtype was 46.0%. Results of the meta analysis showed significant poor survival with relapse (heart rate (HR) 1.59, 95% confidence interval (CI) 1.27 to 1.98) and white blood count (WBC) counts ≥ 50,000 (HR 2.92, 95% CI 1.23 to 4.60). Conclusions The results showed that 5-year survival rates in patients with AML were lower than patients with ALL. The results of this meta analysis strongly support the need for future research, action, and guidance for clinicians to improve health-related quality of life and outcomes for children with leukemia.